Nitrogen-doped graphene with a three-dimensional architecture assisted by carbon nitride tetrapods as an efficient metal-free electrocatalyst for hydrogen evolution - Gangadharan, Pranav K.; Unni, SreeKuttan M.; Kumar, Nandha; Ghosh, Prasenjit; Kurungot, Sreekumar (Chemelectrochem, 2017)
Current polymer membrane-based electrolyzers use Pt as a cathode catalyst for efficient reduction of water. The high cost of Pt-based catalysts forces researchers to develop alternative electrocatalysts. Here, a simple strategy has been proposed to synthesize a metal-free electrocatalyst for the hydrogen evolution reaction (HER) by high-temperature annealing of graphene oxide-coated melamine foam. The prepared catalyst possesses both structural and functional advantages with its three-dimensional (3D) interconnected arms of carbon nitride (CNx) backbone wrapped with nitrogen-doped graphene (N-RGO) sheets (CNx@N-RGO). CNx@N-RGO faces only a 193 mV overpotential to achieve a current density of 10mAcm(-2), which is far superior to the previously reported Pt-free systems. Along with the high exchange current density 34.7 x 10(-6)A cm(-2) and low Tafel slope of 54 mV dec(-1), CNx@N-RGO follows a Volmer-Heyrovsky mechanism for the HER. DFT calculations show that the synergy between CNx and N-RGO facilitates good electrical coupling between the two moieties and provides optimal binding to H+ ions on the catalyst that, in turn, results in efficient reduction of hydrogen ions.
Keywords: carbon nitride; Density functional theory; electrocatalyst; hydrogen evolution reaction; nitrogen doped graphene

Improving the optical and thermoelectric properties of Cs2InAgCl6 with heavy substitutional doping: a DFT insight - Bhamu, K. C.; Haque, Enamul; Praveen, C. S.; Kumar, Nandha; Yumnam, G.; Hossain, Md. Anwar; Sharma, Gautam (RSC Advances, 2021)
The next-generation indium-based lead-free halide material Cs2InAgCl6 is promising for photovoltaic applications due to its good air stability and non-toxic behavior. However, its wide bandgap (>3 eV) is not suitable for the solar spectrum and hence reduces its photoelectronic efficiency for device applications. Here we report a significant bandgap reduction from 2.85 eV to 0.65 eV via substitutional doping and its effects on the optoelectronic and opto-thermoelectric properties from a first-principles study. The results predict that Sn/Pb and Ga and Cu co-doping will enhance the density of states significantly near the valence band maximum (VBM) and thus reduce the bandgap via shifting the VBM upward, while alkali metals (K/Rb) slightly increase the bandgap. A strong absorption peak near the Shockley-Queisser limit is observed in the co-doped case, while in the Sn/Pb-doped case, we notice a peak in the middle of the visible region of the solar spectrum. The nature of the bandgap is indirect with Cu-Ga/Pb/Sn doping, and a significant reduction in the bandgap, from 2.85 eV to 0.65 eV, is observed in the case of Ga-Cu co-doping. We observe a significant increase in the power factor (PF) (2.03 mW m(-1) K-2) for the n-type carrier after Pb-doping, which is similar to 3.5 times higher than in the pristine case (0.6 mW m (-1) K-2) at 500 K.